Implementation of Integrated District Administration Service Policy (Case Study in Plandaan Subdistrict, Jombang Regency) - Mustasfiri Mustasfiri; Sunariyanto Sunariyanto; Slamet Muchsin (Ji_Mild (Jurnal Ilmiah Magister Ilmu Administrasi), 2020)
Abstract This study departs from Minister of Domestic Affairs Regulation Number 4 of 2010 Concerning Integrated District Administrative Service Guidelines (PATEN), this guideline aims to bring services to the public to be fast, easy, affordable, professional so as to encourage the realization of sub-districts as a service center and service node for offices/integrated service agency in the Regency/City, but in the implementation of the Plandaan District, there are still many obstacles, especially in the aspects of the expertise of service implementing officers, internet network problems and, constraints from citizens who are reluctant to take care of their own files.The formulation of the problem in this study is PATEN Services in Plandaan Subdistrict, Jombang Regency, then Implementation of integrated district administration service policy (PATEN) in Plandaan Subdistrict, Jombang Regency, Supporting and inhibiting factors for the successful implementation of integrated district administrative service policy (PATEN) in Plandaan Subdistrict, Jombang Regency. This study uses a qualitative approach, with descriptive research type, while the research location is in the Plandaan District office in Jombang, the data collection technique used is to use interview, observation, and documentation techniques. While the research instruments are the researchers themselves, interview guides, and communication and documentation tools. Analysis of the data of this study uses an interactive model that is data reduction, data presentation, and verification of conclusion data.The results of the study show that if the physical aspects and resource aspects of the Plandaan District office can synergize with the communication aspects, and a good bureaucratic structure is supported by aspects of reliability, direct evidence, responsiveness, assurance and empathy in conducting PATENT services, then the aspect improvement facilities and infrastructure, SOP, and bureaucratic aspects in order to improve the existing service constraint factors can make the quality of services provided to the public be achieved to the maximum and quality. Keywords: Policy implementation, Services, PATEN, District Plandan